Economics of Child Protection: Maltreatment, Foster Care, and Intimate Partner Violence - Doyle, Joseph J. (Annu Rev Econom, 2018)
Violence within families and child neglect are strikingly common: 700,000 children are found to be victims of abuse or neglect in the United States each year; over the course of childhood, 6% of children are placed in foster care, and 18% witness intimate partner violence. These children are at much higher risks of homelessness, criminal justice involvement, unemployment, and chronic health conditions compared to their neighbors. This article reviews the state of the economics literature on the causes and consequences of child maltreatment and intimate partner violence and calls for greater research into interventions aimed at improving child well-being.